Preparation of efficient oligomer-based bulk-heterojunction solar cells from eco-friendly solvents. Issue 38 (18th September 2017) - Popović, Duško; Ata, Ibrahim; Krantz, Johannes; Lucas, Sebastian; Lindén, Mika; Mena-Osteritz, Elena; Bäuerle, Peter
Abstract : A series of A–D–A type co-oligomers used as donors in organic solar cells are presented. Devices prepared exclusively from non-halogenated solvents via doctor-blading gave power conversion efficiencies of up to 7%. Abstract : The field of solution-processable oligomer-based organic solar cells is progressing rapidly. However, common halogenated solvents used in the fabrication of solar cell devices stand out as a growing problem concerning industrial applications. Here, we report on the fabrication and post-treatment of solution-processed bulk heterojunction solar cells exclusively from non-halogenated solvents o -xylene for processing and tetrahydrofuran for solvent vapor annealing (SVA). As donors, we incorporated a series of three different dithieno[3, 2- b :2′, 3′- d ]pyrrole (DTP) containing A–D–A co-oligomers and [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM) as acceptor. The resulting devices exhibited power conversion efficiencies (PCEs) of up to 7.04%. The photoactive layers were probed using absorption spectroscopy, grazing incident X-ray diffraction (GIXRD), and atomic force microscopy (AFM) to clarify the effect of the solvent vapor treatment.